Pengaruh Strategi Word Square Berbantuan Media Gambar terhadap Hasil Belajar Matematika Siswa Kelas IV SD IT Kamiliyah Palembang - Dendi Juniansyah; Nora Surmilasari; Jayanti Jayanti (Departement of Mathematics Education, 2023)
This study aims to prove that there is an influence of the word square learning model on student learning outcomes in mathematics at SD IT Kamiliyah Palembang. The population of this research is all class IV even semester of 2022/2023 academic year. This study uses a purposive sampling technique, which means data collection techniques with certain considerations in taking the sample. The samples in this study were students of class IVA as the control class and students of IVB as the experimental class. This research is a quantitative research with a quasi-experimental type. The research design used in this research is the Post Test Only Control Group Design. In this design there are 2 groups selected randomly (R). Research on class IVB as an experimental class using the word square learning model. Based on the results of the analysis of hypothesis testing on the posttest values ​​of the experimental class and control class using the t-test (Independent sample T-test) with the help of SPSS, the sig. (2-tailed) of 0.000 <0.05. So it can be concluded that Ha is accepted. This means that there is a significant influence of the word square learning strategy assisted by media images on the learning outcomes of Mathematics for class IV SD IT Kamaliyah Palembang. It is suggested that this model can improve students' skills and activeness in answering and solving various questions from easy questions to difficult questions.